Quantitative and Qualitative aspects of Human Resources in Nepal: An Overview - Bista, Binod Kumar (Administration and Management Review, 2009)
Productive output can be achieved by doing things at the right place, in the right time through the right number of those kind of people who are economically most active. It is necessary to anticipate future HR and then develop and implement manpower action plans and programs for being responsive to specific requirements. That is to say, we have to be finally reconciled when the foreseen demands and supply process of manpower is developed with proper planning, great care and attention to meet development and other needs. Administration and Management Review Vol. 20, No. 1, January, 2008, Page 45-51